Prevalencia de desnutrición en pacientes con enfermedad renal crónica terminal en un Hospital Nacional Lima - Perú - Munive-Yachachi, Yveth (2021)
Introduction. Chronic kidney disease (CKD) is a global public health problem characterized by a persistent and progressive deterioration of kidney function. In advanced stage, renal replacement therapy is necessary, which triggers a series of metabolic and nutritional disorders. Objective. To determine the prevalence of malnutrition in patients with terminal chronic kidney disease treated at a national hospital in Lima, Peru. Method. A descriptive study was carried out in patients with CKD, through interviews and anthropometric measurements. The malnutrition and inflammation score (MIS) was used to assess nutritional status. Results. 155 patients with terminal CKD were evaluated, 106 (68.4%) were men. The prevalence of malnutrition was 36%; and for the protein-energy wasting syndrome it was 74%. Conclusions. A considerable percentage of malnourished patients was found, which could be the consequence of various factors that converge in this pathology; the most vulnerable to the development of this complex syndrome were women.